Carbon dioxide emission after application of pig slurry and pig deep-litter - Giacomini, Sandro José; Aita, Celso (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate the carbon dioxide emission to atmosphere after pig slurry and deep-litter application to the soil, along with oat straw with and without soil incorporation. The experiment was carried out on a Hapludalf. The experimental design was a completely randomized one with three replicates. The treatments consisted of application, or not, of pig slurry and pig deep-litter on oat straw, with and without soil incorporation. The measurement of the CO2 emission began after treatment applications and lasted 120 days. Pig manure and oat straw incorporation to the soil increase C-CO2 emission to the atmosphere, compared to the distribution of those organic materials on soil surface. Pig slurry and pig deep-litter application on the straw do not increase CO2 emission to the atmosphere, which indicates that these organic materials do not influence C mineralization present in oat straw.
Keywords: mineralization; straw; no-tillage; minimum tillage